2022
DOI: 10.1002/advs.202106004
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Strategies toward Polysulfides Shuttle Inhibition for High‐Performance Li–S Batteries

Abstract: Lithium–sulfur (Li–S) batteries are regarded as the most promising next‐generation energy storage systems due to their high energy density and cost‐effectiveness. However, their practical applications are seriously hindered by several inevitable drawbacks, especially the shuttle effects of soluble lithium polysulfides (LiPSs) which lead to rapid capacity decay and short cycling lifespan. This review specifically concentrates on the shuttle path of LiPSs and their interaction with the corresponding cell compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
101
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 225 publications
(130 citation statements)
references
References 237 publications
0
101
0
Order By: Relevance
“…The major challenge to be overcome to commericialise lithium-sulphur battery is that known as 'polysulfide shuttling', whereby ions such as Li2S4 migrate to, and poison, the anode, leading to rapid capacity loss. 182 A unique application of EPD has been demonstrated to overcome this challenge. Blanga et al reported the formation of a polysulfide barrier through EPD.…”
Section: Lithium-sulphur (Li-s) Systemsmentioning
confidence: 99%
“…The major challenge to be overcome to commericialise lithium-sulphur battery is that known as 'polysulfide shuttling', whereby ions such as Li2S4 migrate to, and poison, the anode, leading to rapid capacity loss. 182 A unique application of EPD has been demonstrated to overcome this challenge. Blanga et al reported the formation of a polysulfide barrier through EPD.…”
Section: Lithium-sulphur (Li-s) Systemsmentioning
confidence: 99%
“…Lithium (Li) metal possessing a high specific capacity of 3860 mAh g –1 and a low redox potential of −3.04 V versus the standard hydrogen electrode is regarded as the main choice of anode materials in next-generation Li-based batteries, such as Li–S and Li–O 2 batteries . However, safety hazards and severe capacity fading caused by Li dendritic growth have hindered their practical application for almost half a century .…”
Section: Introductionmentioning
confidence: 99%
“…Lithium (Li) metal possessing a high specific capacity of 3860 mAh g −1 and a low redox potential of −3.04 V versus the standard hydrogen electrode is regarded as the main choice of anode materials in next-generation Li-based batteries, such as Li−S and Li−O 2 batteries. 1 However, safety hazards and severe capacity fading caused by Li dendritic growth have hindered their practical application for almost half a century. 2 The uniform Li + ion transportation and mechanical stability of a solid−electrolyte interphase (SEI) layer are the preconditions of dendrite-free Li deposition; 3 however, a conventional in situ formed SEI layer with inhomogeneous structure and composition makes Li + ion flux nonuniform and causes the current density to aggregate on the surface of the anode locally.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, some obstacles seriously hinder the implementation of LSBs, including the low intrinsic electrical conductivity of sulfur and lithium sulde (Li 2 S/Li 2 S 2 ), the undesirable shuttling of soluble intermediate LiPSs between the cathode and anode and a volume expansion of about 80%. These issues result in slow redox kinetics, limited sulfur utilization, irreversible Li anode corrosion and low coulombic efficiency 3,4 and poor cycle stability. [5][6][7] Therefore, developing various catalysts, including metal oxides, 8 suldes, 9 carbides, 10 nitrides and phosphides, 11,12 to anchor LiPSs and accelerate the redox reaction kinetics is the key to realize desirable application of LSBs.…”
Section: Introductionmentioning
confidence: 99%